2016
DOI: 10.1016/j.cell.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA NORAD Regulates Genomic Stability by Sequestering PUMILIO Proteins

Abstract: SUMMARY Long noncoding RNAs (lncRNAs) have emerged as regulators of diverse biological processes. Here we describe the initial functional analysis of a poorly characterized human lncRNA (LINC00657) that is induced after DNA damage, which we termed Noncoding RNA Activated by DNA Damage or NORAD. NORAD is highly conserved and abundant, with expression levels of approximately 500–1,000 copies per cell. Remarkably, inactivation of NORAD triggers dramatic aneuploidy in previously karyotypically-stable cell lines. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
778
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 745 publications
(842 citation statements)
references
References 56 publications
22
778
0
1
Order By: Relevance
“…Their multiple biological activities depend on association with differentially expressed partners, 29 on posttranslational modifications that can be modulated by growth factors, 30 on PUM stability itself, 13 and also on the presence of RNA sponge that binds and sequesters PUM proteins. 27,28 Our data indicate that PUM1 and PUM2 gene expression levels are also regulated along cell differentiation, being maximal in undifferentiated progenitors.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Their multiple biological activities depend on association with differentially expressed partners, 29 on posttranslational modifications that can be modulated by growth factors, 30 on PUM stability itself, 13 and also on the presence of RNA sponge that binds and sequesters PUM proteins. 27,28 Our data indicate that PUM1 and PUM2 gene expression levels are also regulated along cell differentiation, being maximal in undifferentiated progenitors.…”
Section: Discussionmentioning
confidence: 85%
“…18 Unexpectedly, overexpression of PUM1/2 was similarly deleterious for HSPC and leukemic cell survival (data not shown), probably reflecting PUM major contribution to chromosome instability, as recently reported. 27,28 These observations indicate that PUM levels are subjected to fine-tuning to control myeloid cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…The same stoichiometric concerns exist for the cytoplasmic functions of lncRNAs and, in general, the roles of cytoplasmic lncRNAs have been less explored. Some cytoplasmic lncRNAs, including the circular lncRNA CDR1as (Memczak et al, 2013) and NORAD (Lee et al, 2016;Tichon et al, 2016), are abundant enough to bind to and affect the function of RNA-binding proteins (Argonaute and Pumilio, respectively) and thereby modulate their ability to regulate their other targets. Other cytoplasmic lncRNAs have been shown to bind and modulate the stability and translation of other RNAs by base-pairing with them (Carrieri et al, 2012;Gong and Maquat, 2011).…”
Section: Trans-acting Rnasmentioning
confidence: 99%
“…For example, lincRNA-p21 is activated by the tumor suppressor p53, represses the transcription of the genes that interfere with apoptosis, and plays a critical role in p53-mediated apoptosis (12). The long non-coding RNA NORAD is induced after DNA damage, and maintains genomic stability by sequestering PUMILIO proteins (13). We have recently shown that the long non-coding RNA lncUSMycN increases N-Myc mRNA expression by interacting with the RNA-binding protein NonO (14).…”
Section: Introductionmentioning
confidence: 99%